2013
DOI: 10.1007/s10858-013-9717-y
|View full text |Cite
|
Sign up to set email alerts
|

Structure of hen egg-white lysozyme solvated in TFE/water: a molecular dynamics simulation study based on NMR data

Abstract: Various experimental studies of hen egg white lysozyme (HEWL) in water and TFE/water clearly indicate structural differences between the native state and TFE state of HEWL, e.g. the helical content of the protein in the TFE state is much higher than in the native state. However, the available detailed NMR studies were not sufficient to determine fully a structure of HEWL in the TFE state. Different molecular dynamics (MD) simulations, i.e. at room temperature, at increased temperature and using protonproton di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The accuracy with which the molecular model mimics these interactions has an impact on the accumulation behavior of TMAO around proteins and thus on the thermodynamic equilibrium between different protein conformations observed in the simulation. These effects can be quantified using the potential distribution theorem or the Kirkwood-Buff theory. If an atom-based cosolute model has been validated against independent data and turns out to reproduce in addition the macroscopic effect of interest, then it can tentatively be used to interpret this effect in physical terms. Our work thus represents a valuable supplement to the recently performed TMAO force-field comparison reported by Rodrı́guez-Ropero et al, which was mainly focused on the impact of TMAO on the folding equilibrium of a hydrophobic model polymer, but also investigated quantities of aqueous solutions such as surface tension, osmotic coefficient, as well as the transfer free energy of neopentane from pure water to 1 molar TMAO solution.…”
Section: Introductionmentioning
confidence: 81%
“…The accuracy with which the molecular model mimics these interactions has an impact on the accumulation behavior of TMAO around proteins and thus on the thermodynamic equilibrium between different protein conformations observed in the simulation. These effects can be quantified using the potential distribution theorem or the Kirkwood-Buff theory. If an atom-based cosolute model has been validated against independent data and turns out to reproduce in addition the macroscopic effect of interest, then it can tentatively be used to interpret this effect in physical terms. Our work thus represents a valuable supplement to the recently performed TMAO force-field comparison reported by Rodrı́guez-Ropero et al, which was mainly focused on the impact of TMAO on the folding equilibrium of a hydrophobic model polymer, but also investigated quantities of aqueous solutions such as surface tension, osmotic coefficient, as well as the transfer free energy of neopentane from pure water to 1 molar TMAO solution.…”
Section: Introductionmentioning
confidence: 81%
“…Unlike other computational studies of TFE - peptide/protein interactions, , our study attempted to quantify the effect of TFE on helical propensity, and we analyzed this effect in the framework of the Lifson–Roig model and preferential interactions. Although the form of the L–R model used in our study is very approximative, our numerical fits can provide at least qualitative insight into the thermodynamics of the helix–coil transition.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the local structure change relates with the local dynamics or entropy change. [40][41][42] In order to understand the structure and dynamics of hBD-3 and HD5 in both oxidizing and reducing conditions, quasi-harmonic entropy of cysteine residue pairs for both kinds of defensins was calculated using the Wordom program with results shown in Table V. The entropy for the wildtype was calculated based on the microsecond simulation trajectories for both kinds of defensins.…”
Section: Entropy Calculationmentioning
confidence: 99%